THE FORMATION OF MUSEUMS AND INNOVATIVE ACHIEVEMENTS IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses about the organization of virtual museums, the development of museums, the path of development, achievements in this field in Uzbekistan. It also gives information about how much attention is being given to the activity of museums and the significance of these activities to Uzbek youth.